Screening of rose (Rosa species) varieties against two-spotted spider mite (Tetranychus urticae) (Acari: Tetranychidae) and its control* - KAUR, PARAMJIT; DHOORIA, M S; BHULLAR, MANMEET B (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2004 to study susceptibility of 7 rose (Rosa spp.) varieties viz 'Eiffle Tower') 'Gold Tops', 'Kiss ofFire', 'Queen Elizabeth', 'Rakatgandha', 'Sea Pearl' and 'Super Star', to the two-spotted spider mite (Tetranychus urticae Koch) through oviposition response, feeding preference and damage caused by mite on them. Variety 'Sea Pearl' was the least preferred by mite and 'Gold Tops' the most. Five pesticides, viz dicofol, ethion, oxydemeton methyl, propargite, and wettable sulphur, were tested for their effectiveness against eggs of the two-spotted spider mite under laboratory conditions at 27 ± l°e. Dicofol (0.025%) and propargite (0.05%) were found the most effective pesticides as ovicides.